Catalytic oxidation of carbon monoxide from vented gas space heaters using alumina foam supported CuMnOx Nanocatalyst - Alireza Abbasi; Saeed Yosefinejad; Shima Bahrami; Mohamad Hoseini (Shiraz University of Medical Sciences, 2019)
Introduction: Carbon monoxide (CO) is an odorless, tasteless, colorless, and nonirritating poisonous gas, recognized as the silent killer for the 21st century. It is produced during partial combustion of carbon-containing compounds. Improper ventilation and flue installation of vented gas space heaters cause carbon monoxide gas to penetrate the building, leading to many deaths annually. The catalytic oxidation of CO has received great attention due to its applications in different fields. In this study, alumina foam coated by CuMnOx catalyst was used to remove CO from the vented gas space heaters. Method: This is a full-scale experimental study on the outflow from vented gas space heaters. Alumina foam supported hopcalite (CuMnOx) catalyst was synthesized using a co-precipitation method for CO oxidation from THE vented gas space heaters. The XRD and SEM were used to characterize the synthesized catalyst. The concentration of CO was measured by IMR 1500 combustion gas analyzer. Result:  The particle size of the catalyst was in the range of 200-600 nm. XRD showed different crystallizations, and the crystal size was in the range of 20 -120 nm.  There was no significant CO removal in the case of using uncoated alumina foam. Results showed CuMnOx catalyst significantly increased the CO removal. The removal efficiencies were 83% and 89% in heating powers of 2300 and 3200 kcal/hr, respectively. The average CO conversation rate was approximately 60.45 µg/gr.min. Conclusion: CuMnOx coated on alumina has a significant effect on CO removal from the vented gas space heaters. The catalyst and outlet gas temperature were the most important factors affecting CO removal.